A retrospective observational study of genital findings in adult women presenting to a New Zealand Adult Sexual Abuse Assessment and Treatment Service following an allegation of recent sexual assault. (February 2022) - Oliphant, Jeannie; Nicolson, Bridget; Coomarasamy, Christin; Foley, Christine; Laking, Anne
Abstract: Objective: The aim of this study was to report on the prevalence of genital findings documented in women attending a forensic examination following an allegation of recent sexual assault. A secondary aim was to investigate for any associations between genital findings and variables related to population demographics and clinical factors. Study design: A retrospective review of clinical records was undertaken for 593 women, aged between 17 and 45 years of age, who underwent a forensic examination within 72 h following an alleged sexual assault at the Pohutukawa clinic, adult Sexual Abuse Assessment and Treatment Service (SAATS) in Auckland, New Zealand over a four-year period. Statistical analysis to examine for any associations between any documented genital findings and subject variables was performed. Results: The key finding was that 66.4% (394/593) of the women had a normal genital examination. Of the 182 women with genital findings the presence of skin disruption and/or bruising was noted in 21.1% (125/593) and non-specific findings in 9.6% (57/593). 17 women were not included as the genital examination was incomplete. For 9.5% (56/593) of women the presence of abnormal genital skin was documented. From the adjusted odds ratios obtained by multivariate analysis there was a statistically significant association between the presence of genital findings and abnormal skin condition (OR 3.13, p = 0.0004). Conclusion: The study demonstrated that the majority of women seen within 72 h of an alleged sexual assault had a normal genital examination. Given the strength of the association between the presence of genital findings and skin condition, we recommend that documentation of the genital skin condition should become a routine part of a forensic examination following sexual assault. This is particularly important if genital findings are present, in order to present the full complexity of clinical examination findings to the court and provide an expert opinion regarding the limitations of attributing causation.